Return to shooting sports after shoulder surgery: An expert survey - Williams, R. R.; Somerson, J. S. (Journal of Surgical Orthopaedic Advances, 2024)
The authors sent a 13-question web-based survey to all American Shoulder and Elbow Surgeons members regarding a timeline of return to shooting sports after shoulder surgery and received 107 responses from all 50 states and eight from outside the United States. Of the respondents, 74.8% considered their rehabilitation protocol "conservative." Surgeons who considered their rehabilitation protocol to be "aggressive" were more likely to return patients to shooting earlier after rotator cuff repair (p = 0.008), anatomic total shoulder arthroplasty (p = 0.015), and reverse total shoulder arthroplasty (p = 0.003). Most surgeons released their patients after 12 weeks. The majority (95.3%) of respondents were asked by patients about shooting after shoulder surgery. Longer duration of practice correlated significantly with the likelihood of being asked about shooting (p = 0.015). Most surgeons would release their patients to return to shooting sports 12 weeks after surgery. It is unknown how shooting affects implant fixation in vivo.